Multiple α sub-variants and anisotropic mechanical properties of an additively-manufactured Ti-6Al-4V alloy. (20th April 2021) - Zhang, Yinling; Chen, Zhuo; Qu, Shoujiang; Feng, Aihan; Mi, Guangbao; Shen, Jun; Huang, Xu; Chen, Daolun
Abstract: Additive manufacturing (AM) is a promising material processing method which gains significant momentum in the aerospace and biomedical industries. However, the anisotropy in the mechanical properties of additively-manufactured materials is still poorly understood. This study was aimed at elucidating crystallographic feature-anisotropy-mechanical property relationship for a Ti-6Al-4V alloy manufactured via selective electron beam melting (SEBM). Abundant α lamellae with six variants were present inside the columnar prior-β grains with a <100> fiber texture during β→α phase transformation. The six α variants followed the Burgers orientation relationship of 110β //0001α and <1-11>β //<11-20>α . Multiple sub-variants in each α variant were observed for the first time. The anisotropy in the mechanical properties was mainly related to the relative amount of six α variants. While the horizontally-oriented samples had a lower yield strength, they exhibited a higher ductility and longer fatigue life than the vertically-oriented samples. Cyclic softening occurred at higher strain amplitudes, and cyclic stabilization sustained at lower strain amplitudes. Fatigue crack mainly initiated from the specimen surface at lower strain amplitudes, while multiple crack initiation tended to occur at higher strain amplitudes. Crack propagation was characterized by fatigue striations along with some secondary cracks.